Effects of microsurgery on short-term serum neurotransmitter levels and long-term cerebral neurological function in elderly patients with spontaneous intracerebral hemorrhage - Zhang, Yang; Pan, Rujun; Liao, Zhengjian; Yin, Shaoya (Frontiers in Neurology, 2025)
ObjectiveThis study explores the impact of microsurgery on postoperative serum neurotransmitter levels and long-term neurological outcomes in elderly spontaneous intracerebral hemorrhage (SICH) patients.MethodsA single-center, prospective, and single-arm cohort study was conducted, enrolling 106 elderly SICH patients aged ≥60 years who underwent microsurgical hematoma evacuation within 24 h of onset. Serum levels of glutamate (Glu), gamma-aminobutyric acid (GABA), norepinephrine (NE), and serotonin (5-hydroxytryptamine, 5-HT) were measured before surgery and on postoperative day 7. Neurological outcomes were assessed at 180 days using the modified Rankin Scale (mRS) and Glasgow Outcome Scale (GOS). Subgroup analyses were performed based on hematoma volume (≥30 mL vs. <30 mL), hemorrhage location (basal ganglia, thalamus, or lobar), and preoperative Glasgow Coma Scale (GCS) scores (3–8, 9–12, or 13–15). Pearson correlation analysis evaluated the relationship between neurotransmitter levels and outcomes.ResultsOn postoperative day 7, Glu and NE levels decreased, while GABA and 5-HT levels increased. Larger hematoma volume, lobar location, and moderate GCS (9–12) were associated with higher Glu/NE, lower GABA/5-HT, and worse mRS/GOS scores. Glu and NE levels positively correlated with mRS and negatively with GOS (p < 0.05); opposite trends were seen with GABA and 5-HT. A composite neurotransmitter score showed good prognostic accuracy, with an AUC of 0.894 (95% CI: 0.796–0.992) for mRS > 2 and 0.846 (95% CI: 0.782–0.910) for GOS < 4.ConclusionFollowing microsurgical hematoma evacuation in elderly SICH patients, postoperative neurotransmitter profiles were associated with long-term functional outcomes. Persistently high Glu/NE and low GABA/5-HT levels predicted poor recovery, especially in those with large or lobar hematomas.